IMPACTOS SOCIOAMBIENTAIS DE HIDRELÉTRICAS E RESERVATÓRIOS NAS BACIAS HIDROGRÁFICAS BRASILEIRAS - Naime, Roberto (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611706109 This article develops an integrated approach to the issue of environmental impacts of earth damsand large reservoirs of the hidrographic basins. From the integrative concept of geobiossystemasas units capable of expressing homogeneities or enhance physical differences in spatial andtemporal land environment, and territorial units, or geographical maps, the same landscape,defined by the statistical characteristics of the natural physical, chemical or biological, ranked bythe same system of relations. From this starting from conceptualization and literature reviews orreports of environmental impacts, assessments are made on the environmental impacts mostrelevant. We also make a discussion on regulatory frameworks for dams and reservoirs in Braziland a brief analysis of the need for environmental governance in the definition of permanent usesof water resources in river basins.